Nutritional Status, Parenting and Sleep Disorders in Children with Autism Spectrum Disorder (ASD) - Astriyana, Sevy; Amarseto, Binuko; Prabandari, Fatchurrohmah Ines; Tatarina, Meyta (Universitas Muhammadiyah Surakarta, 2025)
Introduction: Autism Spectrum Disorder (ASD) is a neurological disorder characterized by social communication disorders, repetitive behaviors that affect cognition. Children with ASD have the potential to experience nutritional status disorders. Children who experience sleep disorders affect the thinking process and affect negative behavior, and behaviors like children with ASD. Parenting helps deal with emotional instability, and compromise on potentially harmful actions in children with ASD. The purpose of this study is to determine the relationship between nutritional status, parenting style and sleep disorders in children with ASD. Methods: This research method is a descriptive- cross-sectional design with purposive sampling techniques. M-CHAT Screening questionnaire used to diagnose autism. Sleep disorders were measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, the implementation of parenting was measured by the Parenting Styles and Dimensions Questionnaire (PSDQ) and height and weight measurements to determine nutritional status. Results: The results of the study were obtained: 1) poor nutritional status (5%) has sleep disturbance with authoritarian parenting; 2) normal nutritional status (84%) has sleep disturbance (62%) with from parents who apply permissive parenting (50%), democratic (31.25%), authoritarian (18.75%); 3) Excess nutritional status comes from permissive parenting and has sleep disturbances (50%). Conclusions: There was no relation between nutritional status, parenting style and sleep disturbances in children with ASD.